Construction of a Governance Model for Public Education Service Agencies: Analysis of Financial Performance Determination from The Maqasid Syariah Perspective - Hasyim Hasyim; Aan Jaelani; Ayus Ahmad Yusuf; Rochanda Wiradinata (Lembaga Bale Literasi, 2026)
The transformation of State Islamic Religious Colleges (PTKIN) into Public Service Agencies (BLU) demands financial independence while remaining grounded in efficiency and accountability. However, reliance on leadership figures and poor digital system integration often hinders achieving financial independence aligned with public welfare values. This study aims to construct a System-Driven Governance model at UIN Siber Syekh Nurjati Cirebon (UIN SSC), a pilot project for Cyber Islamic University, through the integration of Leadership, Control, and Digital Governance (SEM-PLS) to improve financial performance from a Maqasid Syariah perspective. This quantitative study employed Structural Equation Modeling (SEM-PLS) analysis. A sample of 208 UIN SSC respondents was drawn using a disproportionate stratified purposive sampling technique. Primary data from the questionnaire was integrated with secondary data from Value for Money (VfM) analysis and treasury regulations. The results indicate that Digitalization and Internal Control have a significant impact on Financial Performance (p < 0.05). Conversely, Transformational Leadership does not directly impact financial performance, but it is a key determinant of the success of digital transformation and internal control maturity. This finding marks a deconstruction of the leadership role, shifting from a central figure to a system-reliable one. From the perspective of Maqasid Syariah (Islamic principles), optimal financial performance is a manifestation of Hifdz al-Mal (the principle of good governance), the efficient and accountable use of state finances and assets. Digitalization serves as an instrument of taysir (ease) that increases budget efficiency, while Internal Control ensures the principle of Amanah (accountability) for the benefit of the public (public value). The System-Driven Governance model offers a reconstruction of governance where oversight is embedded in digital platform algorithms, rather than the physical presence of leaders.